2006
DOI: 10.1002/glia.20387
|View full text |Cite
|
Sign up to set email alerts
|

In situ fluorescence imaging of glutamate‐evoked mitochondrial Na+ responses in astrocytes

Abstract: Astrocytes can experience large intracellular Na+ changes following the activation of the Na+-coupled glutamate transport. The present study investigated whether cytosolic Na+ changes are transmitted to mitochondria, which could therefore influence their function and contribute to the overall intracellular Na+ regulation. Mitochondrial Na+ (Na+(mit)) changes were monitored using the Na+-sensitive fluorescent probe CoroNa Red (CR) in intact primary cortical astrocytes, as opposed to the classical isolated mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…We used real-time fluorescence imaging to follow intracellular ionic alterations during glutamate superfusion and studied the impact of glutamate on the metabolism of astrocyte mitochondria in situ. In previous studies, we have shown that the mitochondrial Na ϩ concentration increases as a result of glutamate transporter activity (Bernardinelli et al, 2006). In the present study, using a fluorescent pH biosensor targeted to the mitochondrial matrix, we show that glutamate, released from neurons or applied by superfusion, induces a dosedependent proton transfer into mitochondria that depends on glutamate transporter activity.…”
Section: Introductionsupporting
confidence: 63%
“…We used real-time fluorescence imaging to follow intracellular ionic alterations during glutamate superfusion and studied the impact of glutamate on the metabolism of astrocyte mitochondria in situ. In previous studies, we have shown that the mitochondrial Na ϩ concentration increases as a result of glutamate transporter activity (Bernardinelli et al, 2006). In the present study, using a fluorescent pH biosensor targeted to the mitochondrial matrix, we show that glutamate, released from neurons or applied by superfusion, induces a dosedependent proton transfer into mitochondria that depends on glutamate transporter activity.…”
Section: Introductionsupporting
confidence: 63%
“…Immediately after uncaging, the intracellular Na + level was elevated by adding gramicidin, monensin, and ouabain. The combination of these three ionophores is known to equilibrate the intracellular Na + concentration with extracellular concentration within several minutes (22,30). The influx of Na + from extracellular medium caused the fluorescence inside cells to gradually increase over a time course of 30 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the limited number of Na + sensors, such as sodium-binding benzofuran isophthalate (22), Sodium Green (23), CoroNa Green/Red (24,25), and Asante NaTRIUM Green-1/2 (26), most of them are not selective for Na + over K + (22-25, 27, 28) or have a low binding affinity for Na + (with a K d higher than 100 mM) (25,(27)(28)(29)(30)(31). Furthermore, the presence of organic solvents is frequently required to achieve the desired sensitivity and selectivity for many of the Na + probes (32)(33)(34), making it difficult to study Na + under physiological conditions.…”
mentioning
confidence: 99%
“…The transport of glutamate plus H ϩ against aspartate is electrogenic (3, 59 -61), and the mitochondrial membrane potential may be dissipated by Ca 2ϩ ϩ Na ϩ cycling, with Ca 2ϩ entry along the uniporter, and exit through the NCX coupled to efflux of Na ϩ back to the cytosol through Na ϩ /H ϩ exchange (62,63). This paradoxical effect of Na ϩ would not affect the OGC, which is electroneutral and thus independent upon ⌬p (64,65).…”
Section: Activitymentioning
confidence: 99%